A study of the rates of pore nucleation and pore growth in alumina-based thermal insulation materials - Cheylyitko, Andrey (Eastern-European Journal of Enterprise Technologies, 2016)
The study considers the Gibbs energy change at the time of pore nucleation. An equation is suggested for describing the critical radius of a pore nucleus. Since it is directly proportional to the surface tension, pores are formed in places with density irregularities or fluctuations. An analysis has revealed conditions for a pore to exist, the minimum work for a pore to nucleate, the time necessary for a pore to appear, and the likelihood of a pore nucleation. The undertaken laboratory tests concern the pore formation rate and the pore growth rate in aluminous materials. The study has determined the general dependencies of wetness changes in the material under its heat treatment and the dynamics of porosity changes in an intumescent material. It allows distinguishing between three stages of change in the number of pores in an intumescent alumina-based material: a stage of a declining number of generated pores, a stage of equable reduction of the number of pores, and a stage of pores overgrowth. The obtained results are applicable to such thermal insulation materials as expanded clay and refractory materials as well as other aluminous materials that are produced by swelling. The conducted experiments have identified the main patterns of changes in the number of pores and the total porosity in aluminous materials when they are heat-treated. It has consequently helped develop a system of equations that describe changes in the porosity of an alumina-based material. The devised equations suggest that the number of pores is directly proportional to the heat treatment temperature as well as to the difference between the surrounding pressure and the critical pressure of a pore. Besides, this system of equations can help predict the number of pores in an intumescent material, which facilitates control over thermophysical properties of the material. The research findings are very important for developing new high-intensity technologies in various industries, in particular for improving the existing production technology of thermal insulation materials based on alumina. Besides, the obtained results can help create new insulating materials.